2020
DOI: 10.3390/ijerph17186582
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HVAC-Systems on the Dispersion of Infectious Aerosols in a Cardiac Intensive Care Unit

Abstract: At the end of 2019, a variation of a coronavirus, named SARS-CoV-2, has been identified as being responsible for a respiratory illness disease (COVID-19). Since ventilation is an important factor that influences airborne transmission, we proposed to study the impact of heating, ventilation and air-conditioning (HVAC) with a variable air volume (VAV) primary air system, on the dispersion of infectious aerosols, in a cardiac intensive care unit, using a transient simulation with computational fluid dynamics (CFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 51 publications
(65 reference statements)
3
45
0
1
Order By: Relevance
“…In conclusion, the emergence of SARS-CoV-2 has accelerated the development and adoption of air purification technologies. [4][5][6][7] In this study, viable virus was detected in the control runs without UV-C light activation or HEPA filtration. Using an UV-C light system with and without HEPA filtration eliminated SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In conclusion, the emergence of SARS-CoV-2 has accelerated the development and adoption of air purification technologies. [4][5][6][7] In this study, viable virus was detected in the control runs without UV-C light activation or HEPA filtration. Using an UV-C light system with and without HEPA filtration eliminated SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 91%
“…10 To date, we are unaware of any APS having been directly challenged with SARS-CoV-2 bioaerosols. [4][5][6][7] The APS successfully eliminated the virus within closely defined parameters reaching significance. Future studies should address the impact of APS on SARS-CoV-2 transmission in a clinical environment, considering challenges from virus emissions by patients to airflow patterns.…”
Section: Resultsmentioning
confidence: 99%
“…The implication of this local, in‐room transmission pattern is that the current focus on high‐level air filtration in central HVAC systems is unlikely to be very helpful for COVID‐19 mitigation (17). There are other reasons to filter recirculated air, airborne particulates and pollen, for example.…”
Section: Airborne Transmission and The Role For In‐room Air Disinfectionmentioning
confidence: 99%
“…Seven studies, including modelling (n=4), epidemiological (n=2), and experimental and modelling (n=1) studies, examined the impact of airflow pattern on SARS-CoV-2/COVID-19 (n=6) and SARS-CoV/SARS (n=1). Settings analyzed included airplane cabins, 46 restaurants, [24][25]47 hospitals and healthcare facilities, [48][49][50] supermarkets, 26 and classrooms. 26 Two of the four modelling studies determined that the placement of ventilation grilles was important in the dispersion of infectious particles.…”
Section: Airflow Patternmentioning
confidence: 99%
“…26 Two of the four modelling studies determined that the placement of ventilation grilles was important in the dispersion of infectious particles. 26,48 Results from Shao et al 26 showed that when the supply and exhaust grilles are near the infectious particle emitter, the infectious particles are less dispersed. You et al 46 found the infection risk in an airliner cabin to be lower when displacement ventilation was used compared to mixing ventilation.…”
Section: Airflow Patternmentioning
confidence: 99%